DETERMINAN KADAR GULA DARAH PUASA PADA PENYANDANG DIABETES MELITUS DI WILAYAH KERJA PUSKESMAS KEDU, TEMANGGUNG - Bela Prasasti; Aryanti Setyaningsih (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2026)
ABSTRACTBackground: Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia that can be caused by several factors such as sociodemographic factors, lack of knowledge related to DM, lack of family support, and lack of dietary compliance.Objectives: This study aims to identify determinants that affect blood sugar levels in people with DM in the work area of the Kedu Health Center, Temanggung.Methods: This study used a quantitative method with a cross-sectional design. The sample consisted of 106 people with DM selected using a purposive sampling technique. The inclusion criteria in this study were respondents with DM and were residents in the Kedu Health Center work area, willing to participate as research subjects, and aged 46 to 75 years. Data were collected through a sociodemographic questionnaire to determine gender, age, education level, occupation, and family income. Diabetes Knowledge Questionnaire (DKQ-24) to determine the level of knowledge related to DM. Hensarling Diabetes Family Support Scale (HDFSS) to determine family support. Perceived Dietary Adherence Questionnaire (PDAQ) to determine dietary compliance. In addition, fasting blood sugar measurements were also carried out using a glucometer. Data analysis was carried out with SPSS using univariate analysis, bivariate with chi-square and spearman tests, and multivariate analysis with binary logistic regression.Results: The results showed that 56.6% of respondents had abnormal blood sugar. Bivariate results showed a relationship between sociodemographic factors (age, education level, occupation, and income), level of knowledge about DM, family support, and dietary compliance with blood sugar levels in people with DM (p <0.05). Multivariate analysis showed that the level of knowledge related to DM was the dominant factor affecting blood sugar levels (p = 0.000) and had a risk of 11.975 times experiencing abnormal blood sugar in people who did not comply with the diet.Conclusion: Factors affecting blood sugar levels in people with diabetes mellitus in the Kedu Health Center work area were sociodemographic factors (age, education level, occupation, family income), knowledge related to DM, family support, and dietary compliance. The most dominant factor was knowledge related to DM. Therefore, good DM management is needed to achieve normal blood sugar levels.Keywords : Diabetes mellitus; blood sugar; knowledge; family support; dietary compliance ABSTRAKLatar belakang: Diabetes melitus (DM) adalah penyakit metabolik yang ditandai dengan hiperglikemia yang dapat disebabkan oleh beberapa faktor seperti faktor sosiodemografi, kurangnya pengetahuan terkait DM, kurangnya dukungan keluarga, dan kurangnya kepatuhan diet. Tujuan: Penelitian ini bertujuan untuk mengidentifikasi determinan yang memengaruhi kadar gula darah pada penyandang DM di wilayah kerja Puskesmas Kedu, Temanggung. Metode: Penelitian ini menggunakan metode kuantitatif dengan desain cross-sectional. Sampel terdiri dari 106 penyandang DM dipilih menggunakan teknik purposive sampling. Kriteria inklusi dalam penelitian ini yaitu responden dengan DM dan merupakan penduduk di wilayah kerja Puskesmas Kedu, bersedia berpartisipasi sebagai subjek penelitian, dan berusia 46 hingga 75 tahun. Data dikumpulkan melalui kuesioner sosiodemografi untuk mengetahui jenis kelamin, usia, tingkat pendidikan, pekerjaan, dan pendapatan keluarga. Diabetes Knowledge Questionnaire (DKQ-24) untuk mengetahui tingkat pengetahun terkait DM. Hensarling Diabetes Family Support Scale (HDFSS) untuk mengetahui dukungan keluarga. Perceived Dietary Adherence Questionnaire (PDAQ) untuk mengetahui kepatuhan diet. Selain itu juga dilakukan pengukuran gula darah puasa menggunakan glucometer. Analisis data dilakukan dengan SPSS menggunakan analisis univariat, bivariat dengan uji chi-square dan spearman, serta analisis multivariat dengan regresi logistik biner.Hasil: Hasil penelitian menunjukkan jika sebanyak 56,6% responden memiliki gula darah abnormal. Terdapat hubungan antara faktor sosiodemografi (usia, tingkat pendidikan, pekerjaan, dan pendapatan), tingkat pengetahuan tentang DM, dukungan keluarga, dan kepatuhan diet dengan kadar gula darah penyandang DM (p<0,05). Tingkat pengetahuan terkait DM merupakan faktor dominan yang memengaruhi kadar gula darah (p=0,000) dan berisiko 11,96 kali mengalami gula darah abnormal pada responden di wilayah kerja Puskesmas Kedu. Simpulan: Determinan yang mempengaruhi kadar gula darah pada penyandang diabetes melitis di wilayah kerja Puskesmas Kedu yaitu factor sosiodemografi (usia, tingkat pendidikan, pekerjaan, pendapatan keluarga), pengetahuan terkait penyakit DM, dukungan keluarga, dan kepatuhan diet. Faktor yang paling mendominasi yaitu pengetahuan terkait penyakit DM. Oleh karena itu diperlukan tata kelola DM yang baik untuk meningkatkan pengetahuan terkait DM guna menjaga kadar gula darah normal. Kata Kunci : Diabetes melitus; gula darah; pengetahuan; dukungan keluarga; kepatuhan diet.